2019
DOI: 10.1103/physrevmaterials.3.043605
|View full text |Cite
|
Sign up to set email alerts
|

Enabling QM-accurate simulation of dislocation motion in γNi and αFe using a hybrid multiscale approach

Abstract: We present an extension of the 'learn on the fly' method to the study of the motion of dislocations in metallic systems, developed with the aim of producing information-efficient force models that can be systematically validated against reference QM calculations. Nye tensor analysis is used to dynamically track the quantum region centered at the core of a dislocation, thus enabling quantum mechanics/molecular mechanics simulations. The technique is used to study the motion of screw dislocations in Ni-Al system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The embedding region is then made large enough in order to accommodate far-field deformation. This latter technique, used here, is an example of a hybrid QM/MM simulation [29,30]. In all cluster methods, an additional layer of redundant "buffer" atoms is required in the ab initio cluster simulation to mitigate electronic effects induced by the artificial free surface of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The embedding region is then made large enough in order to accommodate far-field deformation. This latter technique, used here, is an example of a hybrid QM/MM simulation [29,30]. In all cluster methods, an additional layer of redundant "buffer" atoms is required in the ab initio cluster simulation to mitigate electronic effects induced by the artificial free surface of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…This method gave excellent agreement with the fully quantum calculations of the functional group detachment 46 at a fraction of computational cost. Similar QM/MM techniques have been used successfully to simulate crack propagation in silicon, 47,48 dislocation motion in metals 49 and molecular adsorption on a CNT surface. 50,51 In this work, we study how the chemical structure at the CNT-polymer interface determines its failure characteristics by simulating CNT pull-out from a cross-linked PE matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Very few data exist for the glide motion of screw dislocations in pure bcc metals using large supercells and MLIPs [31,34,79]. Both Wang et al [34], using an extended modified EAM potential for bcc V at 77 K, and Maresca et al [79], using a GAP potential for bcc Fe at 200 K, reported that the screw dislocation starts to glide on the (101) plane via double-kink nucleation and growth.…”
Section: Dynamic Screw-dislocation Propertiesmentioning
confidence: 99%
“…In the case of MTPs additionally, it is not possible (like, e.g. for Gaussian processes [31]) to calculate explicitly the correlation between different configurations in the set. The question of a proper training set is thus always central to the construction of an MLIP, as it will fail to provide accurate predictions for underrepresented atomic environments.…”
Section: Training Setmentioning
confidence: 99%